2018
DOI: 10.2478/pjst-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the Axel Paulsen Figure Skating Jump

Abstract: Introduction. Figure skating is a sport discipline requiring a combination of artistic and athletic skills. The triple Axel Paulsen (Axel or A) jump is the most technically difficult jump of all figure skating jumps, which is why it is on the top of the International Skating Union (ISU) Judging System Code of Points (CoP). The purpose of this research was to explore the technical differences between the single Axel (1A), the double Axel (2A), and the triple Axel (3A) and to determine which parameters are the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…Previous investigations determined that stiffness of skating boots influences the habitual movement pattern of skaters. This often results in an inability to use the full range of movement in the joint [3,5,6]. Taking into account that the present study confirms that the height of the jump increases the chance of achieving a higher AOR score, it should be emphasized that training performed in the off-ice conditions should include exercises that emphasize the full range of motion in the joints (especially the ankle joint).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous investigations determined that stiffness of skating boots influences the habitual movement pattern of skaters. This often results in an inability to use the full range of movement in the joint [3,5,6]. Taking into account that the present study confirms that the height of the jump increases the chance of achieving a higher AOR score, it should be emphasized that training performed in the off-ice conditions should include exercises that emphasize the full range of motion in the joints (especially the ankle joint).…”
Section: Discussionsupporting
confidence: 51%
“…Results of the previous studies indicate that performing jumps with one rotation may impact the ankle joint with the force of 3-8 bodyweight (BW). The forces increase with each additional turn [3,4,5]. Further investigations showed that stiffness of skating boots negatively affects the range of motion of the ankle joint.…”
Section: Introductionmentioning
confidence: 99%
“…El patinaje artístico es una disciplina deportiva que combina capacidades artísticas y atléticas (Ionescu & Gugu-Gramatopol, 2014;Mazurkiewicz, Iwanska, & Urbanik, 2018). Puede realizarse sobre hielo o sobre ruedas, pero los elementos realizados en los programas son similares (Dias, et al, 2014).…”
Section: Introductionunclassified
“…One of the most common and fundamental gymnastics and dance movements is leaps. Leaps require complex motor coordination of both upper and lower body segments [1,2]. Moreover, to make it all more interesting and complex, leap performance is in most cases followed by an additional manipulation of the apparatus (ball, rope, hoop, or ribbon), which may involve throwing or passing through it using different techniques.…”
Section: Introductionmentioning
confidence: 99%